Preparation of antibacterial and biocompatible dressing by solid phase dispersion matrix and maceration methods based on lawsone extracted from lawsonia inermis - Fahimeh Imani; Reza Shahhoseini; Mehrorang Ghaedi (Scientific Reports)
Abstract This study focused on extracting and preconcentrating lawsone (2-hydroxy-1,4-naphthoquinone) from Lawsonia inermis leaves to develop an advanced antibacterial polymer wound dressing designed to prevent infections and enhance wound healing. Utilizing biocompatible cellulose acetate as the base polymer, the material was combined with Ag-MOF (silver-metal-organic frameworks) to serve as a nano-carrier for the controlled release of lawsone. Extraction was performed via maceration and QuEChERS methods, with HPLC and UV-Vis spectrophotometry confirming a significantly higher lawsone yield from QuEChERS (57.218 ppm) than maceration (8.205 ppm). Spectrophotometric analysis identified water as the optimal solvent, with QuEChERS achieving an 83% dry extract efficiency. The wound dressings exhibited exceptional hydrophilicity (contact angles of 39.7° for QuEChERS and 57.2° for maceration), high moisture absorption (63% equilibrium rate, 79.42% water fraction), and effective antibacterial activity, particularly against Staphylococcus aureus (17.5 mm inhibition zone for maceration-based extract). Sustained release profiling indicated peak extract concentration (934.124 ppm) after 24 h, while structural analyses (XRD, FTIR, FE-SEM) confirmed optimal physicochemical properties. These findings demonstrate the dressing’s superior exudate management, biocompatibility, and antimicrobial efficacy, positioning it as a promising therapeutic solution for wound care.